2018
DOI: 10.31373/ejtcm/95161
|View full text |Cite
|
Sign up to set email alerts
|

Methods of evaluation of microvascular structure: state of the art

Abstract: Cardiovascular diseases represent the leading cause of death in Western Countries. Among them, a key role is played by arterial hypertension, which causes macro-and microvascular alterations. Specifically, hypertension is associated with structural alterations in the microvessels, such as an increased ratio of the tunica media thickness to internal lumen (M/L ratio) in small resistance arteries and a reduction of capillary density. In order to evaluate the small resistance artery structure, the direct measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…This difference in remodeling may stem from the differences in function and histological structure among microvessels of various sizes. 59…”
Section: Discussionmentioning
confidence: 99%
“…This difference in remodeling may stem from the differences in function and histological structure among microvessels of various sizes. 59…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the caliber of blood vessels that are typically visualized in the two ROIs by the fundus camera, we estimated the average blood vessel diameter in μm. We consider this question important to the original aim of the study because different types of the blood vessels remodel in a different manner, which may be the ultimate cause for different microvascular network patterns in the two ROI in the disease states 6 . To estimate the blood vessel diameters, we used the approach similar to the one applied by Knudtson et al .…”
Section: Methodsmentioning
confidence: 99%
“…Although the remodelling of retinal microvascular network in pathologic conditions affects retina globally, the differences in the extent and type of remodelling among various segments of retinal microvascular network may exist 4,5 . These differences in remodelling may stem from the distinct function and histological structure among microvessels of various size 6 . It has been reported that the diameters of blood vessels generally decrease as their number of branching generations increases 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations